From 2000 years of Ganoderma lucidum to recent developments in nutraceuticals - Bishop, Karen S. (2015)
Medicinal mushrooms have been used for centuries as nutraceuticals to improve health and to treat numerous chronic and infectious diseases. One such mushroom is Ganoderma lucidum, commonly known as Lingzhi, a species revered as a medicinal mushroom for treating assorted diseases and prolonging life. The fungus is found in diverse locations, and this may have contributed to confusion regarding the correct taxonomic classification of the genus Ganoderma. G. lucidum was first used to name a specimen found in England and thereafter was naively applied to a different Ganoderma species found in Asia, commonly known as Chinese Lingzhi. Despite the taxonomic confusion, which has largely been uncorrected, the popularity of Lingzhi has escalated across the globe. The current taxonomic situation is now discussed accurately in this Special Issue on Ganoderma. Today it is a multi-billion dollar industry wherein Lingzhi is cultivated or collected from the wild and consumed as a tea, in alcoholic beverages, and as a nutraceutical to confer numerous health benefits. Consumption of nutraceuticals has grown in popularity, and it is becoming increasingly important that active ingredients be identified and that suppliers make substantiated health claims about their products. The objective of this article is to present a review of G. lucidum over the past 2000 years from prized ancient herbal remedy to its use in nutraceuticals and to the establishment of a 2.5 billion $ (US) industry.